Volume 2: Combustion, Fuels and Emissions, Parts a and B 2012
DOI: 10.1115/gt2012-68792
|View full text |Cite
|
Sign up to set email alerts
|

LES for the Evaluation of Acoustic Damping of Effusion Plates

Abstract: Effusion cooled liners, commonly used in gas turbine combustion chambers to reduce wall temperature, may also help reducing the propagation of pressure fluctuations due to thermoacoustic instabilities.Large Eddy Simulations were conducted to accurately model the flow field and the acoustic response of effusion plates subject to a mean bias flow under external sinusoidal forcing. Even though existing lower order computational models showed good predicting capabilities, it is interesting to verify directly the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Furthermore, each plate has been tested with several blowing ratio conditions (M=1.5, 3, 5). For further details, please refer to Andreini et al [16].…”
Section: Experimental Testsupporting
confidence: 87%
“…Furthermore, each plate has been tested with several blowing ratio conditions (M=1.5, 3, 5). For further details, please refer to Andreini et al [16].…”
Section: Experimental Testsupporting
confidence: 87%
“…(9) and (13). The analytical models give reactances which are linear with frequency and are therefore not capable of reproducing the experimental trends seen here.…”
Section: Orifice Impedance Datamentioning
confidence: 72%
“…Andreini et al developed a compressible Large Eddy Simulation (LES) technique [12] which has been used to study the acoustic damping properties of the multi-perforated plates used as cooling devices in gas turbine combustors. The CFD method also allowed investigation of the effect on the acoustic damping of geometrical details such as the staggering and angle of the holes [13]. Following the work of [4], Mendez et al applied LES to analyse the damping effect of a perforated liner with bias flow [14].…”
mentioning
confidence: 99%
“…As both representations are interchangeable, the scattering matrix coefficients can be computed from the transfer matrix coefficients by a simple algebraic transformation have to be determined experimentally or numerically. Indeed, several studies deduced matrix coefficients for acoustically passive combustor parts of varying complexity, e.g., a single orifice [3], a tandem orifice [4], multiperforated liner plates [5], or a premixed nozzle [6]. The acoustic transfer behavior of swirl generators, which are an unavoidable part in swirl stabilized combustion systems, was numerically determined by Gikadi et al [7] and Ni et al [8].…”
Section: Transfer and Scattering Matricesmentioning
confidence: 99%
“…Experience has shown that this kind of analysis provides not only quantitative data on stability limits and dynamics of a combustion system but also important physical insight [9,[11][12][13][14][15][16]. Several previous studies have concentrated on the transfer or scattering matrices of individual combustor elements such as a flame, a burner, a swirl nozzle, or a dissipative element [3][4][5][6]8,9,11,13,14,[17][18][19]. The present study concerns in an integrated fashion a combustor scattering matrix that includes swirler, injection tube, and flame as well as parts of the combustion chamber, see Fig.…”
Section: Transfer and Scattering Matricesmentioning
confidence: 99%